Adolescent rampant caries - Namita; Rita Rai (Wolters Kluwer Medknow Publications, 2012)
Adolescent rampant caries is a new and growing challenge in Conservative Dentistry. It has the same etiology and pattern as that of nursing bottle syndrome. Herein, a case is presented in which the main cause of rampant caries is the patient's habit of keeping cariogenic food in her mouth and going to sleep. Educating this etiology and introduction of preventive strategies not only assists in meeting the special oral needs of the adolescent population, but also helps to establish lifelong healthful habits.